ESTUDO QUÍMICO E ATIVIDADE LARVICIDA FRENTE AO Aedes aegypti DO ÓLEO ESSENCIAL DAS FOLHAS DE Cinnamomum zeylanicum Breyn (CANELA) - Mendes, Leandra Sofia dos Santos (2012)
In the search for alternative chemical control against the Aedes aegypti mosquito, several studies are developed and encouraged in order to discover new substances of plant origin insecticides. In this work, the extraction and analytical study of the essential oil from leaves of Cinnamomum zeylanicum Breyne (cinnamon), we analyzed the effect of oil larvicide against third stage larvae of the mosquito Aedes aegypti. The essential oil of leaves was extracted quantitatively by steam distillation. The physicochemical properties of essential oil (density, refractive index, solubility, color and appearance) were determined. It was determined the components by gas chromatography coupled to a mass spectrometer. We quantified the major component of essential oil by Gas Chromatography coupled to mass spectrometer. We calculated the oil and standard LC50, besides the confidence limit at 95% probability, using the methods of Reed-Muench (1938) and Pizzi (1950), respectively. The oil yield was 0.79% m/m. We identified four components in the oil, and the majority presence of eugenol was confirmed by analytical technique. The oil larvicidal activity showed a mortality of 50, 60 and 100% at concentrations of 50, 60 and 100 mol L-1, respectively. The essential oil obtained LC50 of 56.49 (±2.25) ppm and the standard of eugenol 79.75 (±2.10) mol L-1. The promising results indicate that the appraised essential oil is consisted of substances that jointly with the major component eugenol provide greater larvicidal effect against Aedes aegypti.